A primeira gibiteca pública sergipana: manual de catalogação de acervos de histórias em quadrinhos - Melo, Ida Conceição Andrade de (2022)
The Gibiteca is a collection specialized in Comics (HQ), which can function as a departmentalization sector of an information unit, a special collection, or even constitute an independent and autonomous information unit. Considering the characteristics relevant to this type of information unit, this dissertation has as its research problem the descriptive and thematic representation, and the organization of physical spaces and virtual environments of these collections. Having as a question: How to catalog HQ collections, considering the specifics of this source, to enable the Organization of Knowledge and Information in Gibitecas? Its general objective was to develop an editorial product that aims to propose a method of descriptive, thematic and indexing (cataloging) representation for the HQ collection of the projected comic book library, with analytical depth and adaptation of the instruments already applied to other sectors of the Library; to apply the principles of the Federal Government's Practical Guide to Ratings to the works, to generate information that facilitates the mediation of reading, with respect to age groups and to suggest informational resources, that is, specialized products and services for comic book readers and aimed at the promotion of reading culture and public reading. Its theoretical framework brought a systematic study of comic books and their characteristics, as well as Information and Knowledge Management in comic books. As a methodology, the study was characterized as bibliographic, with its descriptive and exploratory objectives, qualitative analysis, applied nature, and a case study at the Epiphanio Dória State Public Library, located in Aracaju-SE. As a result, it obtained a bibliographic survey relevant to the descriptive and thematic representation of the comic book item; information on the Collection of Comics at the Epiphanio Dória State Public Library; an analysis of the physical spaces and virtual environments of the main Brazilian comic books and some comic libraries. The product “Catalogation Manual for collections of comics: how to organize a comic book library” presents a normative regarding the descriptive and thematic representation of the comic item, models of labels with indicative classification and signs for works in digital support, guidelines on the organization of the comics. Spaces and environments, indications of cultural actions and animations aimed at comics, and a schedule for programming for events related to the comics. It is concluded that the elaboration of the manual, product of this dissertation, can be established as a management model for implantation and specialized work in other information units, with generalizing, conceptual and updated content.